Identification and generalisability of key causes of challenges in the implementation of IPD contract in construction projects with the perspective of Iran road construction projects. (20th February 2023) - Jahroudi, Mohammadjavad Nasiri; Nani, Mehdi; Safa, Ebrahim; Sadeh, Ehsan
Integrated project delivery (IPD) system is one of the new achievements of the construction industry in the field of contracting and project implementation. Especially infrastructure projects in the construction industry, which tries to improve the project output by integrating the project team and working together between different factors and elements involved in the project. Despite of many advantages and increasing applications of IPD contract method revealed in developed countries, there are so much challenges in using that, due to lack of familiarity and sufficient information, in developing countries such as Iran. In this article, after extensive studies and investigations, the most important causes of challenges in the implementation of IPD contract and its generalisability with the nine principles of this type of contract and their correlation with Pearson statistical method were identified. Then, the challenges identified in IPD with methods Friedman were ranked and the most important items were extracted.